A Characterization of Plaster Of Paris as an Alternative Water-Based Ink Medium for Silk Screen Printing - Sedon, Mohd Fauzi (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates the potential of Plaster of Paris (POP) as an alternative medium for producing water-based screen printing ink. The project is based on the concept of aesthetic experimental to explore different types of print characteristics for instance, consistency, workability, colour densities, and impression qualities. Evaluation measures including medium particle size using Field Emission Scanning Electron Microscopy (FE-SEM) testing, microstructural and chemical composition analysis using Scanning Electron Microscope-Energy Dispersive Spectrometer (SEM-EDS), and toxicity analysis using Inductively Coupled Plasma Optimal Emission Spectrometer (ICPOES). The results showed that the formulated medium has a unique property and provided opportunities in creating different types of luminosity and opacity effects. It also created unique print characteristics which capable to derive a huge aesthetic potential within the context of ideas development, concept and creativity specifically for fine artists and designers.